DNA binding and unwinding by Hel308 helicase requires dual functions of a winged helix domain - Northall, Sarah J.; Buckley, Ryan; Jones, Nathan; Penedo, J. Carlos; Soultanas, Panos; Bolt, Edward L. (Elsevier, 2017)
Hel308 helicases promote genome stability linked to DNA replication in archaea, and have homologues in metazoans. In the crystal structure of archaeal Hel308 bound to a tailed DNA duplex, core helicase domains encircle single-stranded DNA (ssDNA) in a “ratchet” for directional translocation. A winged helix domain (WHD) is also present, but its function is mysterious. We investigated the WHD in full-length Hel308, identifying that mutations in a solvent exposed α-helix resulted in reduced DNA binding and unwinding activities. When isolated from the rest of Hel308, the WHD protein alone bound to duplex DNA but not ssDNA, and DNA binding by WHD protein was abolished by the same mutations as were analyzed in full-length Hel308. Isolated WHD from a human Hel308 homologue (HelQ) also bound to duplex DNA. By disrupting the interface between the Hel308 WHD and a RecA-like domain, a topology typical of Ski2 helicases, we show that this is crucial for ATPase and helicase activities. The data suggest a model in which the WHD promotes activity of Hel308 directly, through binding to duplex DNA that is distinct from ssDNA binding by core helicase, and indirectly through interaction with the RecA-like domain. We propose how the WHD may contribute to ssDNA translocation, resulting in DNA helicase activity or in removal of other DNA bound proteins by “reeling” ssDNA.